Reactive Arthritis Secondary to Cauda Equina Injury following Spine Fracture: A Case Report - Xiao Li; Shaoling Wu; Chao Ma (Case Reports in Orthopedics)
A 38-year-old man presented with a one-month history of muscle weakness and dysesthesia in the lower extremities, urinary retention, and urinary tract infection after lumbar burst fracture resulted from high fall. During the rehabilitation in our hospital, he had arthritis in both the ankle and knee. However, the patient was treated as gouty arthropathy initially. The arthritis was completely remitted in a few days after the patient was diagnosed as reactive arthritis and started with sulfasalazine therapy and there was no recurrence during 4 months of follow-up. Based on this case, early recognition of reactive arthritis is of major importance to avoid delayed initiation of appropriate treatment in the patients with polyarthritis secondary to neurogenic bladder following cauda equina injury after spine fracture.